Aerated concrete applied to sound insulation and heat preservation of floor slab and preparation method of aerated concrete
By introducing silica-alumina porous microspheres and Fe3O4@polypropylene fibers into aerated concrete, using magnetic field directional arrangement and segmented heating treatment to form a gradient pore structure, the problem of poor structural stability of aerated concrete is solved, and better sound insulation and mechanical properties are achieved.
Patent Information
- Application Number
- CN202510808474.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-17
- Publication Date
- 2025-10-14
- Estimated Expiration
- 2045-06-17
AI Technical Summary
The existing aerated concrete floor slabs have poor structural stability, resulting in poor sound insulation and long-term mechanical properties, which affects their service life.
By introducing porous silicon-alumina microspheres and Fe3O4@polypropylene fibers, using a magnetic field to align the fibers, and combining segmented heating and low-temperature initial setting and high-temperature curing, a gradient pore structure is formed to enhance the stability and strength of concrete.
It improves the structural strength and durability of aerated concrete, enhances the sound insulation effect of impact sound, maintains its lightweight characteristics, and extends its service life.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of floor slab concrete, and in particular to aerated concrete used for sound insulation and heat preservation of floor slabs and a preparation method thereof. Background Art
[0002] In the construction industry, impact sound insulation performance is closely related to the sound transmission path, material properties, and structural design. Impact sound generated by floor slabs primarily occurs through two pathways: direct sound transmission, where the impact energy directly impacts the floor surface, inducing structural vibrations that propagate through the floor itself, its connections, and supporting structures to adjacent spaces. Lateral sound transmission, where the vibrations diffuse through non-continuous areas such as floor edges, wall joints, or pipeline holes to adjacent building components, forming "sound bridges." Therefore, impact sound insulation is achieved by blocking the vibration transmission path and dissipating sound energy, requiring the floor slab to possess properties such as high damping.
[0003] In this regard, aerated concrete has been applied to the research and practice of floor sound insulation due to its lightweight and thermal insulation properties. For example, the patent with announcement number CN116290528A proposes a UHPC-based aerated concrete floor and its construction method. Insulation material is used as a template, and truss steel bars are tied upside down in the template so that the upper end of the truss steel bars extends into the template and the lower end is exposed outside the template. Fiber-modified autoclaved aerated concrete material is poured on the side of the template with truss steel bars, and then aerated and cut to form an aerated concrete body with truss steel bars. The aerated concrete body is heated and pressurized to generate strength and melt the template to expose the upper end of the truss steel bars. The truss steel bars are connected to the UHPC bottom liner using snap connectors. Ordinary concrete is then poured on the fiber-modified autoclaved aerated concrete layer with the UHPC bottom liner to form an aerated concrete floor.
[0004] However, existing sound insulation floors that incorporate aerated concrete, such as those described above, still have the following problems: The structural stability of aerated concrete is poor, causing its porous structure to deform over time, thereby affecting the impact sound insulation effect, and also causing the strength of the floor to deteriorate and shorten its service life. Summary of the Invention
[0005] The purpose of the present invention is to solve the problems of poor structural stability of aerated concrete in existing sound insulation floors containing aerated concrete, namely poor long-term sound insulation effect and mechanical properties.
[0006] The present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing aerated concrete for floor slab sound insulation and heat preservation, comprising the following steps:
[0008] S1 uniformly mixes fly ash, sand, phosphogypsum, quicklime, slaked lime, Fe3O4@ polypropylene fiber and aluminum powder according to the quantity, injects into the mold in multiple times, and simultaneously injects the silicon-aluminum porous microspheres, and obtains the initial setting concrete by heating treatment;
[0009] S2 places the initial setting concrete in a magnetic field, applies a uniform magnetic field, and then transfers into a heater for heating treatment, and then uniformly cools at a speed of 5-12 ℃ / h to obtain the aerated concrete.
[0010] Preferably, in step S1, the mass of the silicon-aluminum porous microspheres injected each time is gradually increased in steps.
[0011] Preferably, in step S1, the heating temperature is 40-50 ℃, and the holding time after heating is 1-2 h; in step S2, the heating temperature is 80-95 ℃, and the holding time after heating is 3-5 h.
[0012] Preferably, in step S1, the fiber length of the Fe3O4@ polypropylene fiber is 20-200 mm, and the micropore particle size of the silicon-aluminum porous microspheres is 50-200 μm.
[0013] Preferably, according to the mass fraction, 30-40 parts of fly ash, 25-35 parts of sand, 15-20 parts of phosphogypsum, 10-15 parts of quicklime, 3-5 parts of silicon-aluminum porous microspheres, 3-5 parts of slaked lime, 1-2 parts of Fe3O4@ polypropylene fiber and 0.2-0.5 parts of aluminum powder are included.
[0014] Preferably, the preparation method of the silicon-aluminum porous microspheres comprises the following steps:
[0015] The silicon source, the aluminum source and the surfactant are mixed and uniformly stirred to obtain a silicon-aluminum homogenate, then nano-titanium dioxide is added and ultrasonically dispersed, freeze-dried, and then transferred into a heating furnace for heating calcination to obtain the silicon-aluminum porous microspheres; wherein the molar ratio of the silicon source, the aluminum source and the surfactant is 2.5-3.5:0.8-1.2:0.1-0.2.
[0016] Preferably, the addition amount of the nano-titanium dioxide is 2-10 wt% of the total mass of the silicon-aluminum homogenate.
[0017] Preferably, the freezing temperature is-80 ℃ to-50 ℃, and the freezing time is 0.5-3 h; the calcination temperature is 500-800 ℃, and the calcination time is 1.5-5 h.
[0018] The aerated concrete for floor sound insulation and heat preservation prepared by the above preparation method has a porosity of 75-85%, a compressive strength of ≥5.6 MPa, a flexural strength of ≥5.2 MPa, and an impact sound insulation of ≤62 dB.
[0019] The technical scheme of the present application has the following beneficial effects:
[0020] The present application introduces silicon-aluminum porous microspheres and Fe3O4@ polypropylene fibers into aerated concrete to enhance the stability of the pore structure of the aerated concrete, i.e., to improve the structural strength and durability of the aerated concrete. Specifically, first, by adding silicon-aluminum porous microspheres in stages, uniform secondary pores are formed by using the gas hydrating characteristics of the silicon-aluminum porous microspheres, and the silicon-aluminum porous microspheres serve as a framework to support the primary pores. The gradient pores formed can effectively improve the frequency width of the aerated concrete for absorbing sound waves, and the aerated concrete retains the characteristic of being lightweight. Then, by applying a magnetic field, the magnetic fibers in the raw materials are arranged in the magnetic field in a directional manner, guiding the pores to be distributed along the stress direction, reducing the risk of pore collapse, and the polypropylene in the magnetic fibers has good elasticity, which can weaken the stiffness inside the concrete to improve the sound insulation effect of the aerated concrete on impact sound. In addition, by segmenting the low-temperature initial setting and high-temperature curing, the pore formation process can be optimized and controlled, and the stability of the pores can be enhanced, thereby improving the stability and support strength of the aerated concrete over time. DETAILED DESCRIPTION
[0021] To make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below. Wherein, the specific conditions in the embodiments are not specified, which are carried out according to the conventional conditions or the conditions recommended by the manufacturer; the instruments, devices or reagents raw materials used are not specified by the manufacturer, which are all conventional products that can be purchased in the market.
[0022] The present application provides an aerated concrete applied to floor sound insulation and heat preservation, which comprises, in terms of mass fraction, 30-40 parts of fly ash, 25-35 parts of sand, 15-20 parts of phosphogypsum, 10-15 parts of quicklime, 3-12 parts of silicon-aluminum porous microspheres, 3-5 parts of slaked lime, 1-2 parts of Fe3O4@ polypropylene fiber and 0.2-0.5 parts of aluminum powder.
[0023] The preparation method of the silicon-aluminum porous microspheres comprises the following steps:
[0024] The silicon source, the aluminum source and the surfactant are mixed and stirred uniformly to obtain a silicon-aluminum homogenate; then nano-titanium dioxide is added and ultrasonic dispersed for 30-60 min, and then placed in a freezer at-80℃ to-50℃ for 0.5-3 h, and then dried for 10-12 h; then transferred into a heating furnace and heated to 500-800℃, and calcined for 1.5-5 h to form silicon-aluminum porous microspheres with micropores of 50-200 μm.
[0025] The Fe3O4@ polypropylene fiber is obtained by blending magnetic iron oxide powder with polypropylene and then melt spinning, and the length of the Fe3O4@ polypropylene fiber is 20-200 mm.
[0026] The application of the aerated concrete for floor sound insulation and heat preservation of the application, the preparation method comprises the following steps:
[0027] (1) first, fly ash, sand, phosphogypsum, quicklime, slaked lime, Fe3O4@ polypropylene fiber and aluminum powder are mixed according to the amount, stirred uniformly, and injected into the mold in multiple times, every time the mold is injected, silicon-aluminum porous microspheres are added synchronously, and the addition amount of silicon-aluminum porous microspheres is increased gradually, a gradient content of pores is formed, and heating to 40-50 DEG C, heat preservation treatment 1-2h, in this process, low temperature can promote the slow production of silicon-aluminum porous microspheres, form uniform secondary pores, and the whole material system realizes initial setting.
[0028] (2) 0.5-1T vertical magnetic field is applied, Fe3O4@ polypropylene fiber is arranged along the direction of the magnetic field, longitudinal channels are formed, transverse stress concentration is reduced, and the uniformity and stability of the pores in the aerated concrete are maintained; heating to 80-95 DEG C, heat preservation treatment 3-5h, can make the material system solidify, at the same time, silicon-aluminum porous microspheres continue to produce gas and fill the collapsed pores.
[0029] (3) the material after solidification is placed in a pressure environment of 1-1.5MPa, and is cooled at a uniform speed of 5-12 DEG C / h, which can avoid the damage of thermal stress to the pore structure, until cooling forming, that is, the aerated concrete used as floor can be obtained.
[0030] The aerated concrete prepared by the above raw materials and method has a porosity of 75-85%, a compressive strength of ≥5.6MPa, a flexural strength of ≥5.2MPa, and an impact sound insulation of ≤62dB.
[0031] Example 1
[0032] Step one: 178.5g of tetraethyl orthosilicate TEOS, 75.0g of aluminum nitrate and 22.3g of cetyltrimethylammonium bromide are mixed, stirred at a speed of 200r / min for 45min, and form a silicon-aluminum homogenate; then 31.7g of titanium dioxide powder with an average particle size of 5nm is added to the silicon-aluminum homogenate, ultrasonic dispersion is carried out for 10min, then it is transferred to-50 DEG C and frozen for 45min, and after taking out, it is dried for 10h; finally, it is placed in a heating furnace, heated to 550 DEG C, calcined for 3h, and cooled to room temperature after taking out, to obtain silicon-aluminum porous microspheres, and the average pore size is about 135μm.
[0033] Step two: according to the mass ratio of 1:9, the nanometer magnetic iron oxide powder and the polypropylene powder passing through a 200 mesh sieve are prepared into Fe3O4@ polypropylene fibers with a length range of 40-80mm by melt spinning.
[0034] Step three: 35.8 parts of fly ash, 26 parts of cement sand, 16.5 parts of phosphogypsum, 12 parts of quicklime, 3.5 parts of slaked lime, 1.45 parts of Fe3O4@ polypropylene fiber and 0.3 parts of aluminum powder were taken by mass fraction, stirred at 80 r / min for 45 min, to obtain the initial mixed slurry, ready for use.
[0035] Step four: the initial mixed slurry was injected into the mold in three times, and each time the initial mixed slurry was injected, it was accompanied by the injection of silicon-aluminum porous microspheres, and the mass fraction of the three times of silicon-aluminum porous microspheres injection was 1 part, 2 parts and 3 parts, then heated to 50℃, and the temperature was kept for 1.5h, to form the initial setting concrete with gradient pore volume.
[0036] Step five: the initial setting concrete was placed in a uniform magnetic field device, a 0.8T vertical magnetic field was applied, then it was transferred into a heating box, heated to 90℃, and kept for 3.5h, then it was transferred into a 1.2MPa pressure environment, and cooled at a constant pressure of 8℃ / h, to obtain the aerated concrete material.
[0037] Example 2
[0038] Step one: 178.5g of tetraethyl orthosilicate TEOS, 75.0g of aluminum nitrate and 22.3g of cetyltrimethylammonium bromide were mixed, stirred at 200 r / min for 45 min to form a silicon-aluminum homogenate; then 31.7g of titanium dioxide powder with an average particle size of 5nm was added to the silicon-aluminum homogenate, ultrasonic dispersion for 10 min, then transferred into a-50℃ freezer for 45 min, dried for 10h after taking out; finally placed in a heating furnace, heated to 550℃, calcined for 3h, cooled to room temperature after taking out, to obtain silicon-aluminum porous microspheres, the average pore size was about 135μm.
[0039] Step two: nano-magnetic iron oxide powder and polypropylene powder passing through a 200 mesh screen were taken in a mass ratio of 1:9, and Fe3O4@ polypropylene fiber was prepared by melt spinning.
[0040] Step three: 35.8 parts of fly ash, 26 parts of cement sand, 16.5 parts of phosphogypsum, 12 parts of quicklime, 3.5 parts of slaked lime, 1 part of Fe3O4@ polypropylene fiber and 0.3 parts of aluminum powder were taken by mass fraction, stirred at 80 r / min for 45 min, to obtain the initial mixed slurry, ready for use.
[0041] Step four: the initial mixed slurry was injected into the mold in three times, and each time the initial mixed slurry was injected, it was accompanied by the injection of silicon-aluminum porous microspheres, and the mass fraction of the three times of silicon-aluminum porous microspheres injection was 0.5 parts, 1.5 parts and 2.5 parts, then heated to 50℃, and the temperature was kept for 1.5h, to form the initial setting concrete with gradient pore volume.
[0042] Step five: the initial setting concrete is placed in a uniform magnetic field device, a 0.8T vertical magnetic field is applied; then it is transferred into a heating box, heated to 90℃, and kept for 3.5h, and then it is transferred into a 1.2MPa pressure environment, cooled at a constant pressure of 8℃ / h, to obtain the aerated concrete material.
[0043] Example 3
[0044] Step one: 178.5g of tetraethyl orthosilicate TEOS, 75.0g of aluminum nitrate and 22.3g of cetyltrimethylammonium bromide are mixed, stirred at a speed of 200r / min for 45min to form a uniform slurry of silicon and aluminum; 31.7g of titanium dioxide powder with an average particle size of 5nm is then added to the uniform slurry of silicon and aluminum, ultrasonic dispersed for 10min, and then transferred into a-50℃ freezer for 45min, dried for 10h after taking out; finally, it is placed in a heating furnace, heated to 550℃, calcined for 3h, and cooled to room temperature after taking out, to obtain silicon-aluminum porous microspheres, and the average pore size is about 135μm.
[0045] Step two: according to a mass ratio of 1:9, nanometer magnetic iron oxide powder and polypropylene powder passing through a 200 mesh sieve are prepared into Fe3O4@polypropylene fibers by melt spinning.
[0046] Step three: according to the mass fraction, 35.8 parts of fly ash, 26 parts of cement sand, 16.5 parts of phosphogypsum, 12 parts of quicklime, 3.5 parts of slaked lime, 1.85 parts of Fe3O4@polypropylene fiber and 0.3 parts of aluminum powder are stirred at a speed of 80r / min for 45min to obtain a preliminary mixed slurry, which is ready for use.
[0047] Step four: the preliminary mixed slurry is injected into the mold in three times, and each time of injecting the preliminary mixed slurry is accompanied by injecting silicon-aluminum porous microspheres, and the mass fraction of the three times of injecting silicon-aluminum porous microspheres is 2 parts, 4 parts and 6 parts, then heated to 50℃, and kept for 1.5h, to form the initial setting concrete with gradient pore volume.
[0048] Step five: the initial setting concrete is placed in a uniform magnetic field device, a 0.8T vertical magnetic field is applied; then it is transferred into a heating box, heated to 90℃, and kept for 3.5h, and then it is transferred into a 1.2MPa pressure environment, cooled at a constant pressure of 8℃ / h, to obtain the aerated concrete material.
[0049] Example 4
[0050] Step one: 178.5 g of tetraethyl orthosilicate TEOS, 75.0 g of aluminum nitrate and 17.5 g of cetyltrimethylammonium bromide were mixed and stirred at a speed of 200 r / min for 45 min to form a silicon-aluminum homogenate; 31.7 g of titanium dioxide powder with an average particle size of 5 nm was then added to the silicon-aluminum homogenate and ultrasonically dispersed for 10 min, and then transferred into a freezer at -50°C for 45 min, and then dried for 10 h after being taken out; finally, it was placed in a heating furnace and heated to 500°C for calcination for 1 h, and then cooled to room temperature after being taken out, to obtain silicon-aluminum porous microspheres, and the average pore size was about 135 μm.
[0051] Step two: nano-magnetic iron oxide powder and polypropylene powder passing through a 200-mesh sieve were mixed in a mass ratio of 1:9 to prepare Fe3O4@polypropylene fibers by melt spinning.
[0052] Step three: 35.8 parts of fly ash, 26 parts of cement sand, 16.5 parts of phosphogypsum, 12 parts of quicklime, 3.5 parts of slaked lime, 1.5 parts of Fe3O4@polypropylene fibers and 0.3 parts of aluminum powder were stirred at a speed of 80 r / min for 45 min to obtain a preliminary mixed slurry, which was used as needed.
[0053] Step four: the preliminary mixed slurry was injected into the mold in two times, and each time of injection of the preliminary mixed slurry was accompanied by injection of silicon-aluminum porous microspheres, and the mass fraction of the silicon-aluminum porous microspheres injected in two times was 2 parts and 5 parts, and then heated to 50°C for 1 h of heat preservation treatment, to form a preliminary set concrete with a gradient pore volume.
[0054] Step five: the preliminary set concrete was placed in a uniform magnetic field device, and a vertical magnetic field of 0.8 T was applied; then it was transferred into a heating box and heated to 90°C for 3.5 h of heat preservation treatment, and then transferred into a 1.2 MPa pressure environment for cooling at a constant pressure of 8°C / h, to obtain an aerated concrete material.
[0055] Comparative Example 1
[0056] Step one: 35.8 parts of fly ash, 26 parts of cement sand, 16.5 parts of phosphogypsum, 12 parts of quicklime, 3.5 parts of slaked lime and 0.3 parts of aluminum powder were stirred at a speed of 80 r / min for 45 min to obtain a preliminary mixed slurry, which was used as needed.
[0057] Step two: the preliminary mixed slurry was injected into the mold in three times, and then heated to 50°C for 1.5 h of heat preservation treatment; then it was transferred into a heating box and heated to 90°C for 3.5 h of heat preservation treatment, and then transferred into a 1.2 MPa pressure environment for cooling at a constant pressure of 8°C / h, to obtain an aerated concrete material.
[0058] Comparative Example 2
[0059] Step one: take the nano-magnetic iron oxide powder and polypropylene powder through a 200-mesh sieve in a mass ratio of 1:9, and prepare Fe3O4@polypropylene fibers with a length range of 40-80 mm by melt spinning.
[0060] Step two: take 35.8 parts of fly ash, 26 parts of cement sand, 16.5 parts of phosphogypsum, 12 parts of quicklime, 4 parts of tetraethyl orthosilicate, 3.5 parts of slaked lime, 2 parts of aluminum nitrate, 0.6 parts of cetyl trimethylammonium bromide, 0.2 parts of Fe3O4@polypropylene fibers, and 0.3 parts of aluminum powder, and stir at a speed of 80 r / min for 45 min to obtain a preliminary mixed slurry, which is ready for use.
[0061] Step three: inject the preliminary mixed slurry into the mold three times, and each time of injection of the preliminary mixed slurry is accompanied by injection of silicon-aluminum porous microspheres, and the mass fractions of the three times of injection of the silicon-aluminum porous microspheres are 1 part, 2 parts, and 3 parts, respectively, and then heat to 50℃ and keep for 1.5 h to form a preliminary set concrete with a gradient pore volume.
[0062] Step four: place the preliminary set concrete in a uniform magnetic field device and apply a 0.8T vertical magnetic field, then transfer it into a heating box and heat to 90℃, keep for 3.5 h, and then transfer it into a 1.2MPa pressure environment and cool at a constant pressure of 8℃ / h to obtain an aerated concrete material.
[0063] Test example
[0064] Take the aerated concrete materials prepared in the above examples 1 to 4 and comparative examples 1 to 2 as samples, and measure the mechanical properties and sound insulation effect of the above samples according to the requirements of GB / T 29756-2013 “Hardened mortar flexural and compressive strength test method” and GB / T 19889.6-2005 “Acoustics Building and building element sound insulation measurement”, and the results are as follows in Table 1:
[0065] Table 1 Performance test results of different samples
[0066] Comparison Item Example 1 Example 2 Example 3 Example 4 Comparative Example 1 Comparative Example 2 Porosity (%) 82 71 84 79 48 55 Compressive strength (MPa) 6.2 5.7 5.6 6.0 5.1 5.3 Flexural strength (MPa) 5.5 5.2 5.3 5.5 4.7 4.4 Impact sound insulation (dB) 53 58 57 62 72 70
[0067] From the above test results, it can be found that the aerated concrete materials prepared in examples 1 to 4 have a significantly better overall effect on strength and impact sound insulation than the aerated concrete materials prepared in comparative examples 1 and 2. Therefore, the aerated concrete and the preparation method thereof can significantly improve the sound insulation effect of the aerated concrete in the actual application of the floor, and the strength of the aerated concrete is significantly improved, which can more effectively play the supporting and stabilizing performance required by the floor.
[0068] The above merely describes the preferred embodiments of the present application, and is not used to limit the present application. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing aerated concrete for floor sound insulation and thermal insulation, characterized in that: The steps include: S1: fly ash, sand, phosphogypsum, quicklime, slaked lime, Fe3O4@polypropylene fiber and aluminum powder are mixed according to the amount, injected into the mold in multiple times, and silicon-aluminum porous microspheres are injected at the same time, and heated to obtain initial setting concrete; S2 places the primary setting concrete in a magnetic field, applies a uniform magnetic field, then transfers it to a heater for heating treatment, and then cools it at a uniform rate of 5-12°C / h to obtain the aerated concrete.
2. The method for preparing aerated concrete for floor sound insulation and thermal insulation according to claim 1, characterized in that: In step S1, the mass of the porous silicon-aluminum microspheres injected each time is increased gradually according to a gradient.
3. The method for preparing aerated concrete for floor sound insulation and thermal insulation according to claim 1, characterized in that: In step S1, the heating temperature is 40-50°C, and the holding time after heating is 1-2 hours; in step S2, the heating temperature is 80-95°C, and the holding time after heating is 3-5 hours.
4. The method for preparing aerated concrete for floor sound insulation and thermal insulation according to claim 1, characterized in that: In step S1, the fiber length of the Fe3O4@polypropylene fiber is 20-200 mm, and the micropore particle size of the porous silica-alumina microspheres is 50-200 μm.
5. The method for preparing aerated concrete for floor sound insulation and thermal insulation according to claim 1, characterized in that: Calculated by weight, it includes 30-40 parts of fly ash, 25-35 parts of sand, 15-20 parts of phosphogypsum, 10-15 parts of quicklime, 3-12 parts of silica-alumina porous microspheres, 3-5 parts of slaked lime, 1-2 parts of Fe3O4@polypropylene fiber and 0.2-0.5 parts of aluminum powder.
6. The method for preparing aerated concrete for floor sound insulation and thermal insulation according to claim 5, characterized in that: The preparation method of the porous silicon-aluminum microspheres comprises the following steps: The silicon source, the aluminum source and the surfactant are mixed and stirred to obtain a silicon-aluminum slurry; nano-titanium dioxide is then added, ultrasonically dispersed, freeze-dried, and then transferred to a heating furnace for heating and calcining to obtain the silicon-aluminum porous microspheres; The molar ratio of the silicon source, the aluminum source and the surfactant is 2.5-3.5:0.8-1.2:0.1-0.
2.
7. The method for preparing aerated concrete for floor sound insulation and thermal insulation according to claim 6, characterized in that: The added amount of nano titanium dioxide is 2-10wt% of the total mass of the silicon-aluminum slurry.
8. The method for preparing aerated concrete for floor sound insulation and thermal insulation according to claim 6, characterized in that: The freezing temperature is -80°C to -50°C, and the freezing time is 0.5-3h; the calcination temperature is 500-800°C, and the calcination time is 1.5-5h.
9. Aerated concrete used for sound insulation and thermal insulation of floor slabs, characterized in that: The method is prepared according to any one of claims 1 to 8.
10. The aerated concrete for floor sound insulation and thermal insulation according to claim 9, characterized in that: The aerated concrete has a porosity of 75-85%, a compressive strength of ≥5.6 MPa, a flexural strength of ≥5.2 MPa, and an impact sound insulation of ≤62 dB.
Citation Information
Patent Citations
Aerated concrete floor based on UHPC (Ultra High Performance Concrete) and construction method thereof
CN116290528A
Polypropylene fiber autoclaved aerated concrete (autoclaved lightweight concrete, ALC) plate and preparation method thereof
CN104478466A
Autoclaved aerated concrete block doped with magnetic polypropylene fiber and preparation method of autoclaved aerated concrete block
CN106587777A
Preparation method for aerated concrete slab
CN109456021A
Multi-layer antibacterial headband
CN111567963A
Cited By
Aerated concrete floor support plate as well as preparation method and application thereof
CN122145093A
Aerated concrete floor deck, its preparation method and application
CN122145093B